Electron, hole, and exciton spectra in a quantum wire crossing the quantum well - Makhanets, O.M.; Gryschuk, A.M.; Tkach, M.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The electron, hole, and exciton energy spectra are calculated within the effective mass and rectangular potential approximations for a combined semiconductor nanoheterosystem consisting of a cylindrical semiconductor quantum wire crossing the plane quantum well. It is shown that the electron (hole) in such a system is characterized by five quantum numbers related to five degrees of freedom for a quasiparticle. The dependences of the quasiparticle energy on the quantum wire radius and the quantum well width are researched.